Dental Trauma and Adverse Oral Conditions Practice and Management Techniques - Moolla, Aneesa (Dentistry, 2023)
Holistic dental care includes looking at prevention, treatment, cure and long-term management. This book endeavors to provide readers with information on dental emergencies and dental trauma, with their associated management and other issues. Other relevant conditions that are highlighted include avulsion, orbital trauma, salivary duct cysts and periodontal disease. Information is also included on mental health and quality of life impacts arising for individuals from dental trauma. Teledentistry, which is relevant for all clinicians in the current climate of digital technologies, is also covered. The book is a compilation of work by dental specialists from across the world, including public healthcare professionals in the field of dentistry. It offers updates and reviews on many interesting and complex issues within the practice of dentistry.